2016
DOI: 10.1111/hdi.12494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum and dialysates obtained from chronic hemodialysis patients maintained on high cut‐off membranes on inflammation profile in human THP‐1 monocytes

Abstract: Taken together, these data demonstrate that High cut-off -membranes eliminate a spectrum of mediators from serum into the dialysate that possess proinflammatory properties and may impair cellular viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Several trials have meanwhile provided evidence suggesting that larger pore membranes indeed enhance clearance of different middle molecules, and can reduce inflammation and calcification. A study in hemodialysis patients treated with HCO vs. high-flux membranes demonstrated by exposing THP-1 monocytes their serum or to the dialysate that HCO membranes eliminate a spectrum of pro-inflammatory mediators from serum into the dialysate [ 41 ]. In patients with signs of chronic mild inflammation (C-reactive protein (CRP) > 5 mg/l), use of HCO in series with a low-flux dialyzer resulted in a dampening of systemic inflammation markers such as soluble TNF receptor 1 (sTNFR1), associated with (cardiovascular) outcomes in observational CKD cohorts [ 42 ], but not of expression density of the P-selectin receptor CD162 on monocytes in pre-dialysis blood samples [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have meanwhile provided evidence suggesting that larger pore membranes indeed enhance clearance of different middle molecules, and can reduce inflammation and calcification. A study in hemodialysis patients treated with HCO vs. high-flux membranes demonstrated by exposing THP-1 monocytes their serum or to the dialysate that HCO membranes eliminate a spectrum of pro-inflammatory mediators from serum into the dialysate [ 41 ]. In patients with signs of chronic mild inflammation (C-reactive protein (CRP) > 5 mg/l), use of HCO in series with a low-flux dialyzer resulted in a dampening of systemic inflammation markers such as soluble TNF receptor 1 (sTNFR1), associated with (cardiovascular) outcomes in observational CKD cohorts [ 42 ], but not of expression density of the P-selectin receptor CD162 on monocytes in pre-dialysis blood samples [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of different membrane characteristics could then be evaluated without influences from sequestration. Studies comparing the use of high cut-off versus high-flux dialysis membranes on the cytokine production profile [109] and the angiotensin-system [110] found less inflammation and a modification of the ACE/ACE2 relation on monocytes towards the normal situation. This might be taken as a hint that the alterations in dialysis patients may be improved by dialysis technology that removes middle molecules (15-45 kD molecular weight).…”
Section: The Role Of Hemodialysis Treatment On Monocytes Phenotype and Functionmentioning
confidence: 99%
“…In particular, HCO dialysis cleared β2-microglobulin, sTNF-RI, factor D, and high molecular AGEs better than HF membranes did [200]. The recent report in which exposure to HCO serum markedly lowered the levels of 72 pro-inflammatory transcripts in THP1 cells (including TNF-α and IL-6) compared with exposure to HF serum demonstrated that HCO dialyzers may also directly decrease the inflammatory potential of monocytes and the subsequent calcification of vascular/valvular cells [201]. Indeed, VSMC calcification was 43% lower when the cells were incubated in vitro with HCO dialysis serum, relative to HF dialysis serum; this effect was accompanied by a 26% relative decrease in ALP expression [202].…”
Section: The Impact Of Ckd On Macrophage Functions: Consequences Fmentioning
confidence: 99%